RANCANG BANGUN ROBOT LENGAN DENGAN PENGGERAK SISTEM PNEUMATIK MENGGUNAKAN PLC - Supriyono Supriyono; Muhamad Yusuf; Arief Ainur Rafiq (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2017)
Utilizing of robots is increasing every year, especially in the industrial field. Robotic arm is one type of robot that used in industry. This robotic arm system is used to move an object from one point to another using a gripper. In this research, the pneumatic system is used as the actuator of the robotic arm (manipulator) and Programmable Logic Controller (PLC)is usedas the controller. The results of this prototype research isa robotic arm that can move object from one point to another point that has been determined. Timing diagrams are used to describe the movement of each arm on the robot. From the experimental results of the overall system, the average time of the robotic arm to move one object in one cycle movement is 18.46 seconds, with a settling time of one cycle is 18 seconds.